Topology optimization for continua considering global displacement constraint - Yi, Jijun (Strojniški vestnik, 2014)
This paper presents a topology optimization method for continua that minimizes the volume subject to global displacement constraint. The method uses the p-norm displacement to represent the equivalent maximum displacement so as to avoid non-differentiability of the maximum function. Using nodal densities as design variables, a new topology optimization technique for controlling the global maximum displacement precisely is developed. Several examples are presented to demonstrate the effectiveness of the proposed method for achieving convergent optimal solutions of structures with global displacement constraint.
Keywords: omejitev globalnega pomika; optimizacija topologije; pomik s p-normo; spremenljivka gostote vozlišč